Formation of economic and managerial tools for anti-crisis diagnostics of construction companies - Bolila, N. (Ways to Improve Construction Efficiency, 2019)
The task of the enterprise management is to form an effective management mechanism, to develop measures to overcome financial crises and to eliminate their negative impacts, which requires the need to create a modern economic and management tools for crisis diagnosis of the enterprise. The purpose of the study is to analyze theoretical and methodological approaches of Ukrainian and foreign scientists on the concepts of "crisis management mechanism" at the operational, tactical and strategic levels of the enterprise. The article deals with the theoretical aspects of enterprise crisis management. The purpose and tasks of the crisis management of the construction enterprise are determined. The necessity of formation of modern economic and management tools of anti-crisis diagnostics of the enterprise is substantiated. The author argues that the formation of the mechanism of crisis management of a construction company must take into account the specifics of its activities and general, characteristic of the entire industry, features of construction activity regardless of the objects under construction and their purpose, among which are the following: variability, temporary nature, variety of construction production and the nature of the final products, the technological interconnectedness of all operations, the instability of the ratio of construction work in terms of their complexity and types of extension ohms of construction, the participation of various enterprises in the production of final construction products, the role of climate and local conditions, real estate construction products, long economic cycle and low speed of capital turnover, high cost of construction objects, significant duration of their operation, the need to attract significant amounts of resources, which explains the widespread practice of prepayments and one hundred percent subscription, a high degree of consumer individualization, and more. Consideration of these features in the development of tools for crisis management of construction enterprises requires the development of separate methods and models purely for construction.